Schwann Cell-Derived Exosomes Induce the Differentiation of Human Adipose-Derived Stem Cells Into Schwann Cells - Zhou, Nan; Xu, Zhao; Li, Xiang; Ren, Sen; Chen, Jing; Xiong, Hewei; Wang, Cheng; Guo, Jiahe; Kang, Yu; Chen, Zhenbing; Li, Wenqing; Yang, Xiaofan; et al. (Frontiers in Molecular Biosciences, 2022)
Adipose-derived stem cells (ADSCs) can differentiate into Schwann cells (SCs) at the site of nerve injury, where Schwann cell-derived exosomes (SC-Exos) are suspected to exert an induction effect. Our study aimed to induce the differentiation of ADSCs in vitro using SC-Exos and to investigate the mechanisms involved through miRNA sequencing. Subcutaneous fat was used to extract ADSCs. Exosomes were extracted from Schwann cell lines (RSC96) using ultracentrifugation and were able to be taken up by human ADSCs. After 8 days of induction of ADSCs by SC-Exos, phenotypic characteristics were observed by examining the expression of SC markers (S100ß, NGFR, MPZ, GFAP) through RT-qPCR, Western blot and immunofluorescence. The RNA and protein expression levels of S100ß, NGFR, MPZ and GFAP were found to be significantly higher in the SC-Exo induction group than in the uninduced group, which was also consistent with the immunofluorescence results. Additionally, miRNA sequencing was performed on exosomes-induced ADSCs, followed by bioinformatic analysis and validation of the results. According to the sequencing results, there were a total of 94 differentially expressed miRNAs. Bioinformatics analysis indicated that 3506 Gene Ontology terms and 98 Kyoto Encyclopedia of Genes and Genomes pathways were significantly enriched. Ten miRNAs, 5 target mRNAs and elevated expression of the PIK3CD/Akt pathway were validated by RT-qPCR or Western blot, which is consistent with the sequencing results. Our study demonstrates that the utility of SC-Exos is effective in inducing the differentiation of ADSCs into SCs, in which these validated differentially expressed miRNAs exert a vital effect. This work provides a new paradigm via rationally applying Schwann cell-derived exosomes as a promising therapeutic option for repairing peripheral nerve injury.